Integrated design of processes and products: Optimal renewable fuels. (4th March 2020) - König, Andrea; Neidhardt, Lisa; Viell, Jörn; Mitsos, Alexander; Dahmen, Manuel
Highlights: Integrated process and product design method for cost and GWI minimization. Multi-component biofuels designed for advanced, highly boosted SI engines. Tailor-made fuels contain ethanol, isobutanol, 2-butanone, 2-MF, cyclopentane. Optimal fuel costs of 18–22 $/GJ fuel and GWIs of 39–61 kg CO2eq. /GJ fuel . Simultaneous design rigorously captures benefits of co-producing fuel components. Graphical abstract: Abstract: Integrated product and process design aims at developing innovative products that provide a desired functionality and are produced efficiently. Tailor-made fuels from renewable feedstocks pose a prominent, societally-relevant example. We build upon the integrated design method from Dahmen and Marquardt (2017) and combine it with the production pathway screening tool from Ulonska et al. (2016). We thus design a tailor-made fuel and its optimal production process by minimizing economic and environmental criteria, i.e., cost and global warming impact (GWI). We consider the production of a tailor-made spark-ignition engine fuel from lignocellulosic biomass. Simultaneous process and product design yields optimal multi-component fuels that consist of ethanol, isobutanol, butanone, cyclopentane, and 2-methylfuran with production costs of 18–22 $ per GJ fuel and GWI values of 38–61 kg CO2eq. per GJ fuel . The proposed method and its solution strategies are, in principle, universal and thus also applicable to products other than fuels.